Differential effects of controllable stress exposure on subsequent extinction learning in adult rats - Hadad-Ophir, Osnat; Brande-Eilat, Noa; Richter-Levin, Gal (Frontiers in Behavioral Neuroscience, 2016)
Deficits in fear extinction are thought to be related to various anxiety disorders. While failure to extinguish conditioned fear may result in pathological anxiety levels, the ability to quickly and efficiently attenuate learned fear through extinction processes can be extremely beneficial for the individual. One of the factors that may affect the efficiency of the extinction process is prior experience of stressful situations. In the current study, we examined whether exposure to controllable stress, which is suggested to induce stress resilience, can affect subsequent fear extinction. Here, following prolonged two-way shuttle (TWS) avoidance training and a validation of acquired stress controllability, adult rats underwent either cued or contextual fear-conditioning (FC), followed by an extinction session. We further evaluated long lasting alterations of GABAergic targets in the medial pre-frontal cortex (mPFC), as these were implicated in FC and extinction and stress controllability. In cued, but not in contextual fear extinction, within-session extinction was enhanced following controllable stress compared to a control group. Interestingly, impaired extinction recall was detected in both extinction types following the stress procedure. Additionally, stress controllability-dependent alterations in GABAergic markers expression in infralimbic (IL), but not prelimbic (PL) cortex, were detected. These alterations are proposed to be related to the within-session effect, but not the recall impairment. The results emphasize the contribution of prior experience on coping with subsequent stressful experiences. Moreover, the results emphasize that exposure to controllable stress does not generally facilitate future stress coping as previously claimed, but its effects are dependent on specific features of the events taking place.